MPEG Surround - The ISO/MPEG Standard for Efficient and Compatible Multichannel Audio Coding - Herre, Jürgen; Kjörling, Kristofer; Breebaart, Jeroen; Faller, Christof; Disch, Sascha; Purnhagen, Heiko; Koppens, Jeroen; Hilpert, Johannes; Röden, Jonas; Oomen, Werner; Linzmeier, Karsten; Kok Seng, Chong (Journal of the Audio Engineering Society, 2008)
Finalized in 2006, the MPEG Surround specification enables the transmission of multichannel audio signals at data rates close to those of one- and two-channel systems. This paper describes the technical architecture and capabilities of the specification. Verification tests include several operational modes as they would be used in typical application scenarios. In order to achieve backward compatibility with legacy devices that are not compliant with MPEG Surround, the spatial side information is embedded in either an ancillary part of the downmix bit stream or in a separate stream. This approach is vastly superior to a matrixed system at the comparable data rates.<br
herre_books_journals